Late-onset and classic phenotypes of Fabry disease in males with the GLA-Thr410Ala mutation - Valtola Kati; Hedman Marja; Kantola Ilkka; Walls Susanne; Helisalmi Seppo; Maria Maleeha; Raivo Joose; Auray-Blais Christiane; Kuusisto Johanna (BMJ PUBLISHING GROUP, 2025)
Objective: To present phenotypic characteristics and biomarkers of a family with the rare mutation Thr410Ala of the α-galactosidase A gene (T410A/GLA) causing Fabry disease (FD).
Methods and results: In a woman in her 60s with hypertrophic cardiomyopathy, T410A/GLA was found in screening for variants in 59 cardiomyopathy-related genes. Her son in his 40s, two granddaughters and two great grandsons carried T410A/GLA. The son had a history of hypertension and paroxysmal AF but no microalbuminuria or classic symptoms or signs of FD. Baseline α-galactosidase A enzyme (α-Gal A) activity varied from 0% to 26.5%. Cardiac MRI showed mild Fabry cardiomyopathy (FC). During 11 years of enzyme replacement therapy (ERT), FC progressed and he suffered sudden cardiac death in his 50s. The great grandsons with T410A/GLA had no active α-Gal A, high lyso-Gb3 levels and normal cardiac imaging. They suffered from neuropathic pain and gastrointestinal symptoms and were started with ERT at the age under 10. Granddaughters with T410A/GLA had α-Gal A activities of 8-18 and 10% of normal. The older granddaughter in her 30s was diagnosed with incipient FC. Plasma lyso-Gb3 analogues were elevated, markedly in the elder male with FC and moderately in the elder granddaughter. In young males with classic phenotype, plasma lyso-Gb3 analogues were only slightly elevated.
Conclusions: The T410A/GLA mutation caused late-onset FD with progressive cardiomyopathy in elder male, and classic FD in young males of the same family. Varying levels of α-Gal A and lyso-Gb3 analogues reflected variable phenotype of FD in the family.